The processes of implementing and sustaining an intensive volunteer one-to-one support (doula) service for disadvantaged pregnant women - McLeish, Jenny; Spiby, Helen; Darwin, Zoe; Wilmot, Helen; Green, Josephine (Policy Press, 2016)
'Doulas' (lay women who are trained to support other women during pregnancy, birth and postnatally) can improve outcomes for disadvantaged mothers and babies. This Realist Evaluation study uses qualitative interviews to explore the views of staff, commissioners and local champions about the processes of establishing and sustaining five volunteer doula support projects in England. The six key factors in their successful implementation are: fitting with local commissioning priorities; staff commitment and skills; networking with other agencies; defining and marketing the role; providing strong support for volunteers; and having some costs absorbed by others. The four key factors in sustaining the projects are: finding ways to balance the numbers of referrals and volunteers; shaping the service to local service drivers; constant networking; and creative responses to funding shortages. It is a constant challenge to balance the rate of referrals and the number of trained volunteers within tight budgets and timescales ...